Nilai-Nilai yang Terkadung dalam Penamaan Desa Pacar Peluk di Megaluh Jombang Kajian Antropolingustik - Amik Indrawati; Heny Sulistyowati; Fitri Resti Wahyuniarti (IKIP Budi Utomo Malang, 2022)
This study aims to identify the values ​​contained in the naming of Calon Peluk Village in Megaluh Jombang. This research uses a qualitative descriptive approach with the steps of data collection, data classification, and analysis. data, and draw conclusions. This research then focuses on anthropolinguistic studies that examine the relationship between language and culture, especially the oral tradition of naming the village of Pacar luk in Megaluh, Jombang. In describing the values ​​contained in the naming of the village of Calon Peluk in Megaluh Jombang, the theory of values ​​is used. This research uses descriptive qualitative method. The methods used in data collection are observation methods, interview methods, documentation, and data identification. The observation method is carried out by systematically observing and recording the symptoms investigated. The interview method carried out by the researcher is realized by using structured interviews. Researchers also used the documentation method in the form of recording with a tape recorder / cellphone. The identity of the data is focused on the values ​​and meaning of the naming of Calon Peluk Village in Megaluh Jombang. The results of this study found that there were two values ​​contained in the naming of the Village of Calon Peluk in Megaluh Jombang, namely the value of welfare and the value of peace. The researcher found that the welfare value in the naming of the Girlfriend Village in Megaluh Jombang, namely the welfare value of hard work, the welfare value of mutual cooperation, the welfare value of education, and the welfare value of caring for the environment. The value of peace contained in the naming of the Village of Calon Huddle in Megaluh Jombang is the value of peace such as the value of social solidarity, the value of peaceful harmony, the value of positive peace of mind, and the value of peace in preserving the environment.